APLIKASI PERPUSTAKAAN DIGITAL BERBASIS ANDROID PADA PERPUSTAKAN JURUSAN ILMU KOMPUTER UNIVERSITAS LAMPUNG - Andika Yuda; Kurnia Muludi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The Computer Science Department Library of The University of Lampung has implemented a library information system. However, the library information system is only to simplify the book search process and is not yet able to display book information directly. Based on this system, to carry out borrowing and returning books, they still use manual methods, so that in terms of service time efficiency, of course, this is still less effective. For services to library users to be more effective, a digital library system is needed that can accommodate users' needs to access book collections online. The development of the digital library was made beforehand on a small scale which was specialized in the Computer Science Department, University of Lampung. This digital library was built using android and web-based programming with the Java programming language, Php, and MySQL database. The data collection method used is the observation and literature study method. The results of the literature study are taking references based on books, journals, and the internet which provide information about previous research regarding digital library applications as well as related information about Android, Android Studio, and language. Java programming. The results of this study indicate that the application has been successfully built using an online database, based on Android and can be run on a mobile device so that the application supports it to be used anytime and anywhere and also this library system makes it easy for admins to manage book data and make it easier to create library reports.